RNA Sequencing and Bioinformatics Analysis to Reveal Potential Biomarkers in Patients with Combined Allergic Rhinitis and Asthma Syndrome - Mao ZD; Liu ZG; Qian Y; Shi YJ; Zhou LZ; Zhang Q; Qi CJ (Dove Medical Press, 2023)
Zheng-Dao Mao,1,* Zhi-Guang Liu,1,* Yan Qian,1 Yu-Jia Shi,1 Lian-Zheng Zhou,1 Qian Zhang,1 Chun-Jian Qi2 1Department of Respiratory and Critical Care Medicine, Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, Changzhou, People's Republic of China; 2Central Laboratory, Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, Changzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Chun-Jian Qi, Laboratory of Oncology, Changzhou Second People's Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, 213003, People's Republic of China, Tel +86-519-81087391, Email qichunjian@njmu.edu.cn Qian Zhang, Department of Respiratory and Critical Care Medicine, Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, No. 29 Xinlong Road, Changzhou, 213003, People's Republic of China, Tel +86-519-81087391, Email qianzhang@njmu.edu.cnIntroduction: Combined allergic rhinitis and asthma syndrome (CARAS) is a concurrent clinical or subclinical allergic symptom of diseases of the upper and lower respiratory tract. This study is the first to explore the expression profiles of mRNA, lncRNA, and circRNA in CARAS using RNA sequencing, which may provide insight into the mechanisms underlying CARAS.Material and Methods: Whole blood samples from nine participants (three CARAS patients, three AR patients, and three normal control participants) were subjected to perform RNA sequencing, followed by identification of differentially expressed lncRNAs (DElncRNAs), circRNAs (DEcircRNAs) and mRNAs (DEmRNAs). Then, lncRNA/circRNA-mRNA regulatory pairs were constructed, followed by functional analysis, immune infiltration analysis, drug prediction, and expression validation with RT-qPCR and ELISA.Results: The results showed that 61 DEmRNAs, 23 DElncRNAs and 3 DEcircRNAs may be related to the occurrence and development of CARAS. KRT8 may be implicated in the development of AR into CARAS. Three immunity-related mRNAs (IDO1, CYSLTR2, and TEC) and two hypoxia-related mRNAs (TKTL1 and VLDLR) were associated with the occurrence and development of CARAS. TEC may be considered a drug target for Dasatinib in treating CARAS. Several lncRNA/circRNA-mRNA regulatory pairs were identified in CARAS, including LINC00452/MIR4280HG/hsa_circ_0007272/hsa_circ_0070934-CLC, HEATR6-DT/LINC00639/LINC01783/hsa_circ_0008903-TEC, RP11-71L14.3-IDO1/SMPD3, RP11-178F10.2-IDO1/HRH4, and hsa_circ_0008903-CYSLTR2, which may indicate potential regulatory effects of lncRNAs/circRNAs in CARAS. Dysregulated levels of immune cell infiltration may be closely related to CARAS.Conclusion: The regulating effect of lncRNA/circRNA-immunity/hypoxia-related mRNA regulatory pairs may be involved in the occurrence and development of CARAS.Keywords: combined allergic rhinitis and asthma syndrome, lncRNA, circRNA, immunity, hypoxia